FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI KECAMATAN JATILUHUR KABUPATEN PURWAKARTA - Windari, Lia; Lisnawati, Naintina; Herutomo, Tomi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: High prevalence of anaemia among pregnant women in Indonesia increasing risk of giving birth to low birth weight babies (LBW) and premature. The prevalence of anaemia among pregnant women in Purwakarta Regency was 65% in 2016, whereas in Jatiluhur Health Center reach 5,4%. Objective: Analyze factors that influence the incidence of anaemia among pregnant women in Jatiluhur, Purwakarta. Method: This research used case control design. Subjects were 34 anaemia pregnant women in Jatiluhur Subdistrict, Purwakarta Regency. Data collection using a questionnaire containing questions about characteristics of respondents, distance of the pregnancy, level of education, antenatal care (ANC) visit, knowledge, and adherence of Fe consumption. Analysis data using Chi-Square test. Result: Factors that influence the incidence of anaemia in pregnant women were age (p=0,002, OR=1,956), iron intake (p=0,006, OR=0,16), level of education (p=0,020, OR=0,07), knowledge (p=0,001, OR=1,266), and ANC visit (p=0,001, OR=2,04) whereas the distance of pregnancy (p=0,619, OR=0,942), protein intake (p=0,493, OR=1,193), parity (p=0,494, OR=1,060), LILA (p=0,086, OR=0,658) and adherence of Fe consumption (p=0,0571, OR=0,07) have no influence with the incidence of anaemia in pregnant women. Conclusion: Factors that influence the incidence of anaemia in pregnant women in Jatiluhur Subdistrict Purwakarta Regency were iron intake, age, level of education, knowledge, and ANC visit.